Konsep Kejujuran dan Keadilan dalam Al-Qur’an (Studi Tafsir Tematik) - Ilma Aurelly; Nur Kholillah; Ana Rahmawati (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2024)
This study focuses on the interpretation of the concepts of honesty and justice in the Qur'an which is a key element in islamic interpretation. In the verse of the Qur'an, it highlights the importance of honesty and justice as the foundation in human relations and relationships with Allah SWT. This study aims to deepen our knowledge about the interpretation of verses of the Qur'an related to the theme of "honesty and fairness". In Q.S an-Nisa' (4):105, emphasizes the importance of adjudicating cases based on the revelation of Allah SWT, namely honesty and justice must be used as the basis in every decision. In Q.S an-Nahl (16):90,it is explicitly stated that Allah SWT commands justice and policy (Ihsan). In Q.S al-Muthaffifin (83):1-17, this verse criticizes fraudulent behavior in economic activities, especially in terms of measurements and scales. In Q.S al-An'am (6):152, it gives directions about moral responsibility in maintaining the Trust, especially in managing the property of orphans. The method used in this study is thematic interpretation. According to the study that has been carried out on the concept of honesty and justice in the Qur'an, especially from the four main verses discussed, it can be concluded that islam places two main values in the life of the community. Justice is a universal principle that everyone must upholf, both in word and deed.